Perpanjangan Waktu Perdarahan pada Pemberian Perasan Bawang Merah (Allium ascalonicum) (The Effect of Red Onion Juice (Allium ascalonicum) to Prolongation of Bleeding Time) - Liliani Saputri Lijaya; Winny Adriatmoko; Zainul Cholid (Pustaka Kesehatan, 2014)
Bleeding is one of many deathscauses. In the dentistry, bleeding can be encountered such as post-surgery. Excessive bleeding may be caused by the consumption of drugs or certain foods. Red onion (Allium ascalonicum) is one of vegetables that isconsumed by people. It wasestimated to be able to affect bleeding because containedquercetinwhich effected on adhesion, aggregation, and platelet secretion. This study aimedto determine whether redonion juice couldcause prolongation of bleeding time in wistar rats. This study wasan experimental research laboratory. The researchsampleswere 28 wistar rats,divided into 4 groups. Samples were adapted for 1 week, then they were given the treatment each group, the group I was given distilled water, group II was given red onion juice 0,562 mg/g BB, group III was given red onion juice 1,125 mg/g BB, and the fourth group was given 2,25 mg/g BBred onion juice orally. Then we cut edge 1 cm long rat tail and every 30 seconds the blood that dripped out on absorbent paper until the bleeding stops, so we got the bleeding time in each sample. The results showed that there were significant differences between the four groups of samples. The conclusion of this study wasredonion juice couldcause prolongation of bleeding time in wistar rats, with the greatest prolongation of bleeding time at dosage of 2,25 mg/g BB, then the dosage of 1,125 mg/g BB, and the smallest at 0,562 mg/g BB of dosage. Keywords: bleeding time, platelet, quercetin, red onion